Contributions to reduce the flood problems in critical points of the micro drainage system in the city of Carazinho - Koppe, Carolina Pasquetti; Scortegagna, Vinícius; Meneguzzi, Virgínia; Gil, Anelise Sertoli Lopes; Ferreira, Matheus de Conto; Fiori, Simone; Fernandes, Vera Maria Cartana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
With the emergence of excessive flooding in the urban environment, the need for unconventional drainage control measures within the limitations of conventional solutions becomes evident. In the present study, infiltration trenches and reservoirs that collect and reserve rainwater were designed as control devices, attenuating the socio-environmental impacts caused by waterproofing of urban areas in the hydrological cycle and in the behavior of the hydrographic basins in question. The measurements were made for two flooding points found in the city of Carazinho – RS, located on Marquês do Pombal Street and São Bento Avenue, due to the obstruction of gutters and street inlets, paving and waterproofing of the ground due to urbanization, lack of maintenance and cleaning of the micro drainage system along with the inability of the system to collect all the volume of water from the runoff. The reductions in flow rate in these areas through the use of trenches were 16% and 15% for the first and second flooding point, respectively, while the use of the delay reservoirs together with the infiltration trenches resulted in a 29% reduction in the first flooding point and 27.5% in the second flooding point. Therefore, it is evident that the use of unconventional control measures is vital to the reduction of the peaks of the flow rate and control of the surface runoff.